Comprehensive evaluation of the mechanism of Gastrodia elata Blume in ameliorating cerebral ischemia–reperfusion injury based on integrating fecal metabonomics and 16S rDNA sequencing - Ding, Ximeng; Liu, Zilu; Liu, Yi; Xu, Baiyang; Chen, Juan; Pu, Jingzhe; Wu, Deling; Yu, Hao; Jin, Chuanshan; Wang, Xiaoli (Frontiers in Cellular and Infection Microbiology, 2022)
Gastrodia elata Blume was used to treat stoke and headaches caused by “Feng” for thousands of years. Present study shown a significant effect of Gastrodia elata Blume on improving cerebral ischemia-reperfusion injury (CIRI). However, the mechanism of whether Gastrodia elata Blume improving CIRI by regulating intestinal flora has not been reported until now. This research aimed to comprehensively evaluate the mechanism of Gastrodia elata Blume on CIRI based on fecal metabolomics and 16S rDNA sequencing. The model of rats with CIRI was created based on the Zea Longa method. Enzyme-linked immunosorbent assay (ELISA) was used to monitor the inflammatory factors in rat serum. Damage of brain tissues were observed using HE staining. Cerebral infarction was observed by TTC staining. The balance of intestinal flora in cecal contents of rats were evaluated by high-throughput sequencing. Changes of metabolites in intestinal flora was evaluated by fecal metabolomics through UHPLC-OE-MS. The area of brain necrosis, cerebral infarction volume and the contents of inflammatory factors in CIRI rats can be effectively reduced after oral administration of Gastrodia elata Blume. CIRI can cause disturbances in the intestinal flora and its associated metabolites. Gastrodia elata Blume can significantly regulate the composition of the intestinal microflora. It reversed CIRI-induced changes in the levels of multiple intestinal bacteria, including Prevotellaceae, Coriobacteriaceae; Prevotella, Gamma proteobacteria unclassified, Barnesiella, Escherichia, Shigella; uncultured Shigella sp, Flavonifractor sp, Escherichia sp. enrichment culture clone NBAR004, Veillonella sp. R-32, and Lactobacillus intestinalis. The levels of metabolites in cecal contents were disturbed in rats with CIRI, including amino acid, purine and sphingolipid metabolism. The changes level of biomarkers in amino acid metabolism induced by CIRI was significantly reversed after treatment with Gastrodia elata Blume. Correlation studies show that: Prevotellaceae was significantly positively correlated with IL-6, and Lactobacillus intestinalis and L-phenylalanine was negative interrelated to IL-1β. Beta-glycerophosphoric acid was significantly negative interrelated to hs-CRP. And there were significantly negative correlated between L-Phenylalanine and Lactobacillus intestinalis, beta-glycerophosphoric acid and Prevotellaceae. Gastrodia elata Blume protected against CIRI, which may be related to improved intestinal microflora composition and metabolism, resulting in decreased inflammation.